2010
DOI: 10.1007/s10709-010-9439-y
|View full text |Cite
|
Sign up to set email alerts
|

hAT transposable elements and their derivatives: an analysis in the 12 Drosophila genomes

Abstract: Transposable elements (TEs) comprise a significant fraction of the genome, and some models of the TE "life cycle" suggest that, in the last phases of the cycle, TEs should be represented, in the genomes, by inactive and degenerated copies. In this study, we analyzed, using a bioinformatics approach, the autonomous hAT elements and their derivatives (active non-autonomous, MITE relatives and degenerated copies) in 12 Drosophila genomes. We found 28 hAT elements that had derivatives. Most copies had features tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…They are short sequences with no coding capacity and conserved TIRs that often reach high copy numbers in the genomes and are found within or near genes (Feschotte and Pritham 2007). They were first discovered in plants (Bureau and Wessler 1992) but are also found in several animal genomes, including Drosophila (Holyoake and Kidwell 2003; Ortiz et al 2010; Dias and Carareto 2011; Deprá et al 2012; Rius et al 2013). The origin of some MITE families is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…They are short sequences with no coding capacity and conserved TIRs that often reach high copy numbers in the genomes and are found within or near genes (Feschotte and Pritham 2007). They were first discovered in plants (Bureau and Wessler 1992) but are also found in several animal genomes, including Drosophila (Holyoake and Kidwell 2003; Ortiz et al 2010; Dias and Carareto 2011; Deprá et al 2012; Rius et al 2013). The origin of some MITE families is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the target site of 28 hAT elements, including derivatives, in 12 Drosophila species revealed a target site specificity requiring the nucleotide residues T and A at positions 2 and 7, respectively (de Freitas et al 2010). This strong specificity of nucleotide positions could not be observed in the sequence logo generated from the TSD of 84 BvhAT and BvhATpin transposons.…”
Section: Discussionmentioning
confidence: 93%
“…Phylogenetic studies showed related elements forming a monophyletic group composed of hAT2_AG and Herves from A. gambiae , hAT-1_Dsi (Drosophila simulans , Drosophila sechellia , Drosophila melanogaster , Drosophila mauritiana and Zaprionus indianus ; this element was also called hosimary by Deprá et al ., (2010)), homo2 (Drosophila mojavensis ), howilli1 (Drosophila willistoni ) and hAT-1DP (Drosophila persimilis and Drosophila pseudoobscura ) (de Freitas Ortiz and Loreto, 2009;Deprá et al ., 2010;de Freitas Ortiz et al ., 2010;Arensburger et al ., 2011). This group will be referred to herein as the Herves -like elements.…”
Section: Introductionmentioning
confidence: 99%
“…The MnRs in the 3′ subterminal region consist of 28 nucleotides. The same array of minisatellites is present in two related hAT elements: hAT1-Dp of D. pseudoobscura and hopers1 of D. persimilis (de Freitas Ortiz et al ., 2010). However, the transposase sequence of the Herves -like TEs present in D. willistoni , D. pseudoobscura and D. persimilis show a general divergence of 0.28, whereas the 5′ MnRs are highly conserved, showing divergence of 0.05.…”
Section: Introductionmentioning
confidence: 99%